Meningkatkan Kemampuan Kognitif Anak Melalui Metode Eksperimen Bermain Warna - Agustina, Dela; Nurwita, Syisva; Imran, Ranny Fitria (Early Childhood Research and Practice, 2024)
This study aims to improve children's cognitive abilities through the color play method in children aged 4-5 years at PAUD Al- Huda, Kemang Manis Village, Pino Raya District, South Bengkulu Regency. This type of research is classroom action research (PTK) which is a collaborative researcher working with class teachers, the subjects of this research are 4-5 year old children consisting of 7 boys and 8 girls. Data collection methods used observation sheets and documentation of this research were carried out in two cycles, each cycle was carried out twice a meeting. The results showed that playing colors can improve children's cognitive. which can be seen in the observation sheet which shows an increase in each cycle. Cognitive development of children by playing colors in cycle I meeting I got a percentage of 39.44% with criteria starting to develop (MB) in cycle I meeting II the results of the action reached 58.27% with kireteria developing as expected (BSH) because the results of the study have not reached the expected criteria, the researchers continued in cycle II there are also research results in cycle II meeting I percentage obtained 73.05% with criteria developing as expected (BSH) while the results in cycle II pertmuan II reached the specified completeness of 96. 66% with the criteria for developing very well (BSB), so this research was stopped in cycle II pertemaun II.